Heart Rate Fluctuation and Mortality in Critically Ill Myocardial Infarction Patients: A Retrospective Cohort Study - Guo, Qi; Li, Hongwei; Ouyang, Huijun; Sun, Runlu; Wang, Junjie; Wu, Maoxiong; Pan, Yue; Wang, Jingfeng; Zhang, Yuling (Frontiers in Cardiovascular Medicine, 2021)
Background: Whether heart rate (HR) fluctuation after admission has an impact on the outcomes of critically ill myocardial infarction (MI) patients in intensive care unit remains unknown. Methods: A total of 2031 MI patients were enrolled from the Medical Information Mart for Intensive Care (MIMIC-III) database. HR fluctuation was calculated as the maximum HR minus the minimum HR in the initial 24 hours after admission. Participants were divided into 3 groups, namely, low HR fluctuation (< 30 beats per minute (bpm)), medium HR fluctuation (30-49 bpm), and high HR fluctuation (≥ 50 bpm). The main outcomes were 30-day and 1-year mortality. Cox regression and restricted cubic spline model were used. Results: Each 10-bpm increase in HR fluctuation was associated with a higher risk of 30-day mortality and 1-year mortality, with adjusted hazard ratios of 1.122 (95% CI, 1.083-1.162) and 1.107 (95% CI, 1.074-1.140), respectively. Compared with the low HR fluctuation group, the high HR fluctuation group suffered a significantly higher risk of mortality after adjustment, with hazard ratios of 2.156 (95% CI, 1.483-3.134) for 30-day mortality and 1.796 (95% CI, 1.354-2.381) for 1-year mortality. A typical J-type curve was observed in restricted cubic splines for the association between HR fluctuation and 30-day or 1-year mortality of MI patients, with the lowest risk on the HR fluctuation of 30 bpm. Sensitivity analyses emphasized the robustness of our results. Conclusions: This retrospective cohort study revealed an independent positive association between HR fluctuation and 30-day and 1-year mortality in critically ill MI patients, which warrants further investigation.